Characteristics of prefrontal activity during emotional and cognitive processing in patients with bipolar disorder: A multi-channel functional near-infrared spectroscopy study - Mao, Mengchai; Chen, Guifang; Feng, Kun; Xu, Dongsheng; Hua, Xuyun; Shan, Chunlei; Liu, Pozi (Frontiers in Neuroscience, 2022)
Bipolar disorder (BD) is a recurrent chronic mental disorder with a broad profile of functional deficits including disturbed emotional processing and cognitive impairments. The goal of current study was to further explore the underlying neural mechanism of dysfunction in BD patients from a comprehensive perspective of both cognition and emotion. Forty-six clinical BD patients and forty-five healthy controls performed emotion induction task and verbal fluency task, with frontal activity measured by functional near-infrared spectroscopy (fNIRS). Our results show distinct hemodynamic activity in prefrontal region during emotional and cognitive processing between BD patients and healthy controls. BD patients exhibit valence-dependent PFC hemodynamic response to emotional stimuli, with bilateral frontal hypoactivity indicating decreased positive reactivity and left frontal hyperactivity increased negative reactivity. On the other hand, BD patients showed impaired performance with bilateral frontal hypoactivity during verbal fluency task. Taken together, frontal dysfunction of cognition and emotionality in BD patients probed by fNIRS would be a potential biomarker in clinical assessment.